(untitled) (Research, Society and Development, 2022)
The world scenario as a result of COVID-19, required the careful recommendation for the population to stay at home, to perform social isolation and to avoid agglomerations. In this context, residents of multiprofessional health residency programs continued to carry out their professional activities, demanding physical and psychological efforts to face the pandemic. The measures to contain the spread of the virus influenced behavior changes. This study aims to verify the perception of changes in habits of students of the Multiprofessional Residency at the Federal University of Triângulo Mineiro, during the first three months of the COVID-19 pandemic. This is a cross-sectional, descriptive and quantitative study, with the participation of 27 residents, who answered an online questionnaire. The results showed that the regular practice of physical activity decreased and screen time increased in the residents’ perception. Regarding the dietary pattern, there was no perception of changes. It is concluded that there was a change in the habits of the Multiprofessional Residency students according to their perceptions, during the first three months of the COVID-19 pandemic when compared to the previous period.